Cellular context determines DNA methylation profiles in SWI/SNF‐deficient cancers of the gynecologic tract. Issue 2 (25th March 2022) - Kommoss, Felix KF; Tessier‐Cloutier, Basile; Witkowski, Leora; Forgo, Erna; Koelsche, Christian; Köbel, Martin; Foulkes, William D; Lee, Cheng‐Han; Kolin, David L; von Deimling, Andreas; Howitt, Brooke E
Abstract: SWI/SNF (SWItch/Sucrose Non‐Fermentable) complex deficiency has been reported in a wide variety of cancers and is often associated with an undifferentiated phenotype. In the gynecologic tract SWI/SNF‐deficient cancers are diagnostically challenging and little is known about their cellular origins. Here we show that undifferentiated endometrial carcinoma (UDEC), SMARCA4‐deficient uterine sarcoma (SDUS), and ovarian small cell carcinoma, hypercalcemic type (SCCOHT) harbor distinct DNA methylation signatures despite shared morphology and SWI/SNF inactivation. Our results indicate that the cellular context is an important determinant of the epigenetic landscape, even in the setting of core SWI/SNF deficiency, and therefore methylation profiling may represent a useful diagnostic tool in undifferentiated, SWI/SNF‐deficient cancers. Furthermore, applying copy number analyses and group‐wise differential methylation analyses including endometrioid endometrial carcinomas and extracranial malignant rhabdoid tumors, we uncover analogous molecular features in SDUS and SCCOHT in contrast to UDEC. These results suggest that SDUS and SCCOHT represent chromosomally stable SWI/SNF‐deficient cancers of the gynecologic tract, which are within the broader spectrum of malignant rhabdoid tumors. © 2022 The Authors. The Journal of Pathology published by John Wiley & Sons Ltd on behalf of The Pathological Society of Great Britain and Ireland.